Synthesis of slightly < 111 >-oriented 0.65Pb(Mg1/3Nb2/3)O-3-0.35PbTiO(3) ceramic prepared from fine powders - Araujo, E. B.; Reis, R. N.; Guarany, C. A.; Meneses, C. T.; Sasaki, J. M.; Souza Filho, A. G.; Mendes Filho, J. (Elsevier B.V., 2007)
Slightly < 111 >-oriented 0.65Pb(Mg1/3Nb2/3)03-0.35PbTiO(3) ceramic was prepared using fine powders obtained by means of an alternative and promising chemical oxide precursor method. High quality samples with improved structural, microstructural, dielectric and ferroelectric properties were obtained. The dielectric constant value (epsilon similar to 2577) measured at 1 kHz is compared to unpoled < 112 > grain-oriented ceramics while the remanent polarization (P-r similar to 19-1 mu cm(-2)) is compared with random grain-oriented ceramics. These results point out the viability to produce ferroelectric PMN-PT ceramics of very good quality using powder precursors prepared from this chemical method. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: ceramics; chemical synthesis; ferroelectricity